DNA-based Approach to Wildlife Conservation: What Can and Can’t be Done? - Dmitry M. Schepetov (Пернатые хищники и их охрана, 2018)
In many cases field biology can greatly benefit from use of modern genetic methods and ready-to-use test systems, promoting ease of organism identification and quantitative means to assess population structure and sizes: Vast DNA sequence databases and available lab protocols make it possible to identify given organisms when methods of classic taxonomy are unavailable. With additional research or priorly available genomic data, population genetics methods allow to investigate beyond existing reproductive barriers and recover gene flow rates between populations. At the same time, forensic science has lots of well established procedures, proven to be robust and easy to reproduce. DNA extraction protocols for trace material can be adopted for animal droppings, hair and other cases where direct or invasive tissue sampling is restricted. Moreover, principles of laboratory individual identification and kinship measurement, initially developed for humans, can be easily transferred to other species.